The Role of Teachers in Cultivating Elementary School Students' Interest in Learning: in Mathematics Learning - Sumarno (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
Abstracts This article examines in depth the strategic role of teachers in fostering elementary school students' interest in mathematics. In the context of 21st-century education and the current digital era, teachers are required not only to deliver material but also to act as facilitators, motivators, classroom managers, and moral role models capable of creating a learning atmosphere that is enjoyable and relevant to students' real lives. This study uses a descriptive qualitative approach with secondary data sources in the form of relevant journals and books. The results of the study indicate that the role of teachers is crucial in fostering students' interest in learning through a contextual, interactive, and adaptive learning approach to individual students' needs. Strategies used by teachers, such as math games, project-based learning, and the use of educational technology, can stimulate curiosity and increase student engagement in the learning process. In addition, collaboration with parents and emotional support from teachers are important factors in building student self-confidence and learning motivation. This study also highlights the importance of teacher reflection on the effectiveness of the methods used and the need for ongoing training to improve the quality of learning. In conclusion, teachers have an integral role in fostering elementary school students' interest in mathematics through a creative, relevant, and student-centered approach, which directly impacts their academic achievement and character development.